Relationship between knowledge and fast food with obesity in adolescents - lestari, hariati; Handayani, Listy; Nurfadilah H, Siti (CORE JOURNAL, 2023)
Obesity is a risk factor of degenerative diseases which is a public health problem that covers almost the entire life cycle including adolescents. Consumption of fast food is suspected as one of the triggers of obesity in adolescents. Purpose: The purpose of this study was to find out the relationship of knowledge and fast food consumption with the incidence of obesity among adolescents in Kendari City, 2021. Method: A quantitative study with cross sectional design was conducted in December 2021 in the Kendari City area, Southeast Sulawesi. The results of the study: based on bivariate analysis showed that of 397 samples of good fast food diet as many as 151 people (38%) normal category and as many as 86 people (21.27%) who have a very good diet category normal and about 23 people (0.3%) have a diet that is not good category obesity. Based on bivariate analysis after conducting a statistical test with the Chi-Square test obtained p= =0,538> 0.05 for knowledge and p = 0.007 < 0.05 for fast food consumption. Conclusion: So it can be concluded that there was not relationship between knowledge with the incidence of obesity in adolescents and there was a significant relationship between fast food consumption with the incidence of obesity in adolescents.